DESCRIPTION OF INCREASING VOCABULARY IN SPEECHLESS PRESCHOOL CHILDREN - Shoahmedova Surayyo Kamilovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses the general and special didactic principles, shape, content, and methods of developing children’s speech in the visual process.